Susceptibility to the collapse of karst dolines in siliciclastic rocks in the municipality of Chapada dos Guimarães (State of Mato Grosso, Brazil) - Kuhn, Caiubi Emanuel Souza [UNESP]; Pires, Renan Rodrigues; Vieira Reis, Fábio Augusto Gomes [UNESP]; Dos Santos Corrêa, Claudia Vanessa [UNESP] (Revista Brasileira de Geomorfologia, 2021)
This work aims to describe a karstic system in siliciclastic rocks of Ponta Grossa Formation, in the urban perimeter of the municipality of Chapada dos Guimarães (State of Mato Grosso, Brazil), in addition to conducting an analysis of the susceptibility to collapse in the study area. It was used as a study method the processing of satellite images available in Google Earth Pro® in ArcGIS® and description and mapping of features in the field. Two conduits were identified, two water resurgences and four dolines, two of which occurred close to residences and two in an area without occupation, with native vegetation. Dolinas 1, 2 and 4 are possibly interconnected by two conduits, which together have a length of just over 400m, the first two of which are in the perimeter of urban occupation. Next to the dolina 1, it is possible to observe in homes cracks formed by the block rotation of the room due to the repression caused by the cavity. Dolina 1 and 2 collapsed in the last 5 years and were filled by landfill by the city hall. Dolinas 4 and 3 and the two water resurgences are in an area without residential occupation, which still has preserved vegetation. The set of processes related to the development of the features was discussed throughout the work and related to the actions and measures provided for in the civil Protection and Defense Policy. The results suggest a relationship between the development of the karst system and the formation of an oxisol and demonstrate the need for further studies to understand this evolution. The work proposes a map of susceptibility to collapse, considering the density of karst features and the possible path of the ducts that interconnect them. In addition, the territorial ordering of the area must consider the fragility of the karst system and susceptibility to collapse.
Suscetibilidade ao colapso de dolinas cársticas em rochas siliciclásticas no município de Chapada do Guimarães (MT, Brasil)
Keywords: Karstic system; Natural disasters; Risk area